An ultrathin high-performance heat spreader fabricated with hydroxylated boron nitride nanosheets. (10th March 2017) - Fu, Li; Wang, Ting; Yu, Jinhong; Dai, Wen; Sun, Hongyan; Liu, Zhiduo; Sun, Rong; Jiang, Nan; Yu, Aimin; Lin, Cheng-Te
Abstract: An ultrathin, highly thermally conductive heat spreader has been fabricated by layer-by-layer stacking of hydroxylated boron nitride nanosheets (HBNNS) for the first time. HBNNS were prepared by a molten hydroxide-assisted liquid exfoliation from hexagonal boron nitride powder. The as-prepared heat spreader of HBNNS exhibits a high thermal conductivity of 51.1 W m −1 K −1 along the in-plane direction, and can be further enhanced 14% by annealing for de-hydroxylation. This heat spreader with 10–30 µ m in thickness possessed excellent thermal stability with negligible weight loss at wide temperature range up to 700 °C, resulting in promising applications for heat dissipation in electronic components operated at high working temperature.